2009
DOI: 10.1038/ncb1987
|View full text |Cite
|
Sign up to set email alerts
|

The let-7 target gene mouse lin-41 is a stem cell specific E3 ubiquitin ligase for the miRNA pathway protein Ago2

Abstract: The let-7 miRNA and its target gene Lin-28 interact in a regulatory circuit controlling pluripotency. We investigated an additional let-7 target, mLin41 (mouse homologue of lin-41), as a potential contributor to this circuit. We demonstrate the presence of mLin41 protein in several stem cell niches, including the embryonic ectoderm, epidermis and male germ line. mLin41 colocalized to cytoplasmic foci with P-body markers and the miRNA pathway proteins Ago2, Mov10 and Tnrc6b. In co-precipitation assays, mLin41 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
247
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(259 citation statements)
references
References 48 publications
11
247
1
Order By: Relevance
“…To date, a limited number of studies have addressed the functional role of PTMs of miRNA pathway machinery. In particular, several PTMs to Argonaute have been characterized (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). However, little is known about the identity and functional significance PTMs in other components of miRISC.…”
mentioning
confidence: 99%
“…To date, a limited number of studies have addressed the functional role of PTMs of miRNA pathway machinery. In particular, several PTMs to Argonaute have been characterized (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). However, little is known about the identity and functional significance PTMs in other components of miRISC.…”
mentioning
confidence: 99%
“…126 Another member of this family, TRIM71-itself a miRNA target, has been shown to be involved in a complex network of interactions with the miRNA pathway (reviewed in Ecsedi and Grosshans 127 ). TRIM71 has been proposed to target Ago2 for proteasomal degradation in mouse embryonic stem cells and neural progenitor cells, 128 but this claim was later challenged with the suggestion that it in fact enhances miRNA function through its interaction with miRISC, possibly by exerting additional translational repression itself. 101 Moreover, although TRIM71 was also shown to be inactive in neural progenitor cells as a factor mediating Ago2 ubiquitination, it does affect AKT signalling, 129 which may in turn affect Ago2 function, as discussed above.…”
Section: Regulation Of Mirisc and Its Functional Diversitymentioning
confidence: 99%
“…For example, several TRIM-NHL proteins (including Drosophila Brat, Mei-P26, and Wech/Dappled; C. elegans NHL-2 and LIN-41; or mammalian TRIM2, TRIM3, TRIM32, and TRIM71) were found associated with RNA-protein complexes (RNPs) (Kanai et al 2004;Duchaine et al 2006;Neumuller et al 2008;Hammell et al 2009;Rybak et al 2009;Schwamborn et al 2009;Chang et al 2012;Li et al 2012Li et al , 2013Loedige et al 2013), and, in some cases, these interactions were shown to be dependent on either the RNA (Hammell et al 2009;Chang et al 2012;Li et al 2012) or the respective NHL domain within the RNP (Neumuller et al 2008;Schwamborn et al 2009;Chang et al 2012;Loedige et al 2013). In addition to Brat, Mei-P26 and TRIM71 were also recently shown to repress translation (Chang et al 2012;Li et al 2012Li et al , 2013Loedige et al 2013), and C. elegans LIN-41 and human TRIM71/ LIN-41 regulate expression of the transcription factors LIN-29 and EGR1, respectively, possibly at the level of translation (Slack et al 2000;Worringer et al 2014).…”
Section: Org Downloaded Frommentioning
confidence: 99%